MARKET & INCOME SHIFTS IMPACT OF 2D-DIGITAL ILLUSTRATORS IN THE GENERATIVE AI ERA IN SOCIAL MEDIA PEERS - Iqbal Oktavialdi; Mochamad Rizal Yulianto; Istian Kriya Almanfaluti; Bayu Hari Prasojo (Journal of Artificial Intelligence and Digital Economy, 2025)
Objective: This study aims to examine the impact of generative artificial intelligence (AI) on the income sustainability of digital illustrators, focusing on the challenges, adaptations, and market shifts within the digital art ecosystem. Method: A qualitative descriptive approach was employed, utilizing data triangulation through interviews with digital illustrators and their clients to capture both producer and consumer perspectives. Results: The findings indicate that generative AI has reshaped the digital illustration market by influencing demand patterns, client preferences, and competition. Illustrators face declining commissions and changing community dynamics but adopt adaptive strategies such as diversifying platforms, enhancing portfolios, and maintaining online visibility to sustain income. Meanwhile, clients balance efficiency and cost against the perceived authenticity of human-made art. Novelty: This research provides an integrated understanding of the dual perspectives of illustrators and clients, offering empirical evidence of how human creativity, authenticity, and relational trust continue to serve as key differentiators in the era of AI-driven creative production.